2019
DOI: 10.1111/jam.14274
|View full text |Cite|
|
Sign up to set email alerts
|

Survey of antimicrobial susceptibility of bacterial pathogens isolated from dogs and cats with respiratory tract infections in Europe: ComPath results

Abstract: Aims To present antimicrobial susceptibilities for bacteria from dogs and cats with respiratory tract infection (RTI) across Europe in 2013–2014 and compare with data from 2008–2010. Methods and Results Minimal inhibitory concentrations were determined for 464 isolates following Clinical and Laboratory Standards Institute standards using antibiotics approved for RTI treatment. Where possible, susceptibility was calculated using predominantly human‐derived breakpoints whilst some antibiotics had no breakpoints.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
6
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 28 publications
5
21
6
4
Order By: Relevance
“…In this study, 57.5% (42/73) of the strains had MDR phenotype, also confirmed by the detection of AR genes. The majority of the resistant strains 35/42 (83%) resulted positive for mecA gene, associated with oxacillin resistance; this result is in concordance with a previous study which revealed a 100% of mecA gene amplification in MRSP strains [41]. A large portion of isolates showed a pattern of resistance against β-lactams, macrolides, and fluoroquinolones.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 57.5% (42/73) of the strains had MDR phenotype, also confirmed by the detection of AR genes. The majority of the resistant strains 35/42 (83%) resulted positive for mecA gene, associated with oxacillin resistance; this result is in concordance with a previous study which revealed a 100% of mecA gene amplification in MRSP strains [41]. A large portion of isolates showed a pattern of resistance against β-lactams, macrolides, and fluoroquinolones.…”
Section: Discussionsupporting
confidence: 90%
“…aureus isolates were resistant to benzylpenicillin, which is very low compared to the prevalence of penicillin resistance in international surveillance of S . aureus from other host species in Europe, including cattle (25% resistance; [ 22 ]), dogs (65.2% resistance; [ 23 ]) and people (78% resistance in nasal commensal S . aureus ; [ 24 ]).…”
Section: Discussionmentioning
confidence: 99%
“…prevalence of penicillin resistance in international surveillance of S. aureus from other host species in Europe, including cattle (25% resistance; [22]), dogs (65.2% resistance; [23]) and people (78% resistance in nasal commensal S. aureus; [24]). Penicillin is among the most widely used antimicrobials in British sheep flocks [25], and remains the drug of first choice for bacterial infections in food-producing animals, including sheep, in Norway [26].…”
Section: Plos Onementioning
confidence: 99%
“…This group comes in intimate contact with humans and pet contact can lead to bacterial spread to humans (Lloyd, 2007). In particular, E. coli is a common pathogenic agent isolated from pets (Mathers et al, 2015) and is often present in dogs and cats with urinary tract infections (UTIs), pyometra and respiratory tract infections (Karkaba et al, 2019;Moyaert et al, 2019). Multidrug resistance (MDR) E. coli isolates have emerged in companion animals in the United States and Europe (Morrissey et al, 2016), but data for China is lacking.…”
Section: Introductionmentioning
confidence: 99%